The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1193/092113eqs256m
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Collapse Probability of Base-Isolated Buildings considering Pounding to Moat Walls using the FEMA P695 Methodology

Abstract: The collapse probability of two three story base-isolated buildings considering pounding to moat walls is examined using the methodology in FEMA P695. The superstructure models consist of a steel intermediate moment frame and a steel ordinary braced frame designed for the same seismic hazard. The behavior of these buildings under various ground motions is first examined, and it is found that the more rigid braced frame results in larger displacements demands on the isolation system, increasing the potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…If isolator device is tested following test specification regulated in ASCE 7-16 as well as existing manufacture qualification control program and standard, and test results indicate stable hysteresis behavior and required capacities for the isolation system, it is recommended to use β TD = 0.1–0.2 (FEMA, 2009; Masroor and Mosqueda 2015). If the prototype isolator testing program and the quality of isolator specimen are not well documented or the behavior of isolator device, especially under extreme displacement range is not well understood, a larger β TD value should be used.…”
Section: Determination Of System Uncertainty βTotmentioning
confidence: 99%
See 1 more Smart Citation
“…If isolator device is tested following test specification regulated in ASCE 7-16 as well as existing manufacture qualification control program and standard, and test results indicate stable hysteresis behavior and required capacities for the isolation system, it is recommended to use β TD = 0.1–0.2 (FEMA, 2009; Masroor and Mosqueda 2015). If the prototype isolator testing program and the quality of isolator specimen are not well documented or the behavior of isolator device, especially under extreme displacement range is not well understood, a larger β TD value should be used.…”
Section: Determination Of System Uncertainty βTotmentioning
confidence: 99%
“…A 3D numerical model of the BI-IMRF was developed in OpenSees (Masroor and Mosqueda, 2013). The study uses the nonlinear version of this model for conducting IDA and modifies the superstructure to be elastic for determining isolator capacities following the proposed procedure.…”
Section: Design Example Considering the Proposed Proceduresmentioning
confidence: 99%
“…5,6 Moat wall pounding can induce very large accelerations and drift demands, diminishing the effectiveness of the isolation system. [7][8][9][10][11] Figure 1 shows prototypical deformation patterns for three types of buildings: a traditional fixedbased building, a base-isolated building with no impact, and a base-isolated building with impact. In general, a baseisolated building will behave like a rigid body if there is no impact.…”
Section: Introductionmentioning
confidence: 99%
“…If impact occurs, however, the structure temporarily loses the isolation benefits and will undergo deformations akin to a fixed-based building. Recent studies 9,[12][13][14] indicate that if the moat wall clearance is not sufficiently large, or if the isolation system is not adequately restrained, the probability of collapse of a base isolated building exceeds the limitations targeted by current design standards.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the forces from moat impact amplified story drift and accelerations responses and could induce yielding in the superstructure, although no collapse was observed in the testing. Using a model for the moat impact developed from their experimental testing, Masroor and Mosqueda looked at the collapse probability of braced and moment frame buildings, with general bilinear isolators. Cutfield et al looked at the same braced frame structure with the included moat impact to investigate the effect of moat impact on life cycle cost.…”
Section: Introductionmentioning
confidence: 99%